What is behind the seeming cessation of the increase in sleep medicine consumption in Finland during the last years? - Erkki Kronholm; Juha Markkula; Lauri J. Virta (SAGE Publishing, 2012)
In Finland, between 2003 and 2010 and parallel to the increase in the prevalence of insomnia-related symptoms among the general population, there has been a cessation of growth and even a decrease in the consumption of traditional hypnotics. The reasons behind this seemingly paradoxical situation are not known. We analyzed trends over the period 2000-2010 in the estimated consumption of traditional hypnotics and some new drugs that are destined for use in insomnia treatment. We used the annual wholesale statistical database compiled by the Finnish Medicine Agency, FIMEA, and data from the Finnish Drug Prescription Register. We found evidence to support two parallel trends in Finnish outpatient care. First, there seems to be a trend in which physicians increasingly comply with official guidelines for insomnia treatment, which partly accounts for the decrease in the consumption of traditional hypnotics. Second, at the same time, the first trend seems to be resulting in an increasing trend to treat insomnia patients with some new drugs that were not originally developed for insomnia treatment by prescribing these non-hypnotic drugs in small, sub-clinical doses. The current trend in practice may have contradictory effects on the treatment of insomnia. The long-term consequences of using low doses of drugs other than hypnotics to treat insomnia are not known and the situation should, therefore, be followed-up in subsequent studies. However, pharmacological treatment should never be a substitute for non-pharmacological treatments of insomnia.